Use of Luminex MagPlex Magnetic Microspheres for High-Throughput Spoligotyping of Mycobacterium tuberculosis Isolates in Port-au-Prince, Haiti - Ocheretina, Oksana (American Society for Microbiology, 2013)
Genotyping of Mycobacterium tuberculosis strains became indispensable for understanding tuberculosis transmission dynamics and designing measures to combat the disease. Unfortunately, typing involves sophisticated laboratory analysis, is expensive, and requires a high level of technical expertise, which limited its use in the resource-poor countries where the majority of tuberculosis cases occur. Spoligotyping is a PCR-based M. tuberculosis complex genotyping method with advantages of technical simplicity, numerical output, and high reproducibility. It is based on the presence or absence of 43 distinct “spacers” separating insertion elements in the direct repeat region of the M. tuberculosis genome. The spoligotyping assay involves reverse hybridization of PCR products to the capture spacers attached to nitrocellulose membranes or to microspheres. Here we report modification of the classic 43-spacer method using the new generation of Luminex multiplexing technology with magnetic microspheres. The method was successfully established and validated on strains with known spoligotypes in our laboratory in Haiti. The distribution of spoligotypes determined in a collection of 758 recent M. tuberculosis isolates was in accordance with previous data for Haitian isolates in the SITWITWEB international database, which were obtained with the traditional membrane-based method. In the present form, spoligotyping may be suitable as a high-throughput, first-line tool for genotyping of Mycobacterium tuberculosis in countries with limited resources.